Complicity without connection or communication - Abigail Barr; Georgia Michailidou (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2016)
We use a novel experiment to investigate whether people aim to coordinate when, to do so, they have to lie; and are more willing to lie when, in doing so, they are aiming to coordinate with a potential accomplice, i.e., another with whom coordination would be beneficial and who is facing the same individual and mutual incentives and the same moral dilemma. We find that people often aim to coordinate when they have to lie to do so and that having a potential accomplice increases willingness to lie even when that potential accomplice is a stranger and communication is not possible.
Keywords: C90; C91; C92; D83; 330; complicity; lying; coordination; die rolling task